Genome-wide association study of body fat distribution identifies adiposity loci and sex-specific genetic effects - Mathias Rask-Andersen (Nature Portfolio, 2019)
Obesity and the distribution of fat within the body are risk factors for cardiometabolic diseases. Here, Rask-Andersen et al. perform GWAS for bio-electrical impedance measurements in UK Biobank participants and identify 29 novel independent loci for fat distribution and a high degree of sex-heterogeneity.